Needs Analysis for Corporate LSP Programs: A Case Study of the Use of Best Practices - Aguilar-Sánchez, Jorge (Instituto Tecnológico de Costa Rica, 2025)
The present case study follows best practices in needs analysis to improve a customer service training program for EFL Spanish speakers. Data was obtained from a semi-structured interview, administered to a course designer, and survey and group interview, directed to eleven customer service representatives and their trainer. This study was conducted in three stages. The first stage analyzed and detailed the best practices regarding the conduction of needs analysis on available literature. The second stage was an interview with a curriculum designer and expert in the field. This stage aimed to identify the best practices in conducting needs analyses in second language acquisition course design, specifically language for specific purposes. The last stage focused on a needs analysis that included the best practices resulting from the analysis of the literature and the data obtained from the interview experts. Results showed that, in corporate curricula, modifications must match learners’ needs to improve curriculum effectiveness. Failure to do so may result in inefficiencies in the curriculum. The researchers conclude that appropriate needs analysis and the use of best practices are imperative to improve the acquisition of a language.